RETFAL: Real-Time Feedback System in Active Learning - Alnahidh , Mohammed A.; Li, Alice S.; Soh , Ben; AlZain, Mohammed A. (International Journal of Language and Literary Studies, 2022)
There are numerous difficulties and challenges faced by teachers in getting real-time feedback from students during lectures in active learning. Three different educational technologies will be investigated in this paper regarding their efficiency and cost effectiveness: (1) Wireless Systems; (2) Tablet Systems; and (3) Audio-Visual Systems. To that end, we propose a new system called Real-Time Feedback in Active Learning system (RETFAL), which is a phone-based application with a view to assist educators in getting real-time feedback. The RETFAL system is implemented on the Android Studio platform using the Java programming language. We validate our RETFAL system using usability testing via an online survey and a face-to-face survey. Finally, we do a comparative study involving the RETFAL system and the LearnStar system in terms of effectiveness and performance. We find that our proposed RETFAL system performs better than the LearnStar system in terms of efficiency and cost-effectiveness with regard to real-time feedback. With RETFAL, we anticipate the performance of students can be improved with effective real-time feedback in active learning.